Copper-doping effects in electronic structure and spectral properties of SmNi5 - Knyazev, Yu.V.; Lukoyanov, A.V.; Kuz’min, Yu.I.; Kuchin, A.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The electronic structure and optical properties of the SmNi5–xCux (x = 0, 1, 2) compounds are studied. The band spectra of the studied intermetallics were calculated with LDA+U+SO method supplementing the local density approximation with a correction for strong electron interaction on the shell of the rare-earth element. Optical properties were studied by ellipsometry method in the wide wavelength range. It was found that the substitution of copper for nickel leads to local changes in the optical conductivity spectra. Both the spectroscopic measurements and theoretical calculations demonstrate the presence of a broad absorption band around 4 eV associated with the Cu 3d → Ni 3d electron transitions and increasing with the grown of copper content. The experimental dispersion curves of optical conductivity in the interband absorption region were interpreted using the results of the calculations.